The Use of the Wheel of Names in Learning Indonesian Text Material Description "Standard Words and Non-Standard Words" Class VII Smp Negeri 12 Dumai - Emi Puspita Sari (Journal of Social Research, 2022)
Background: In Indonesian learning, creative and innovative media are needed so that students are not saturated in learning in the classroom. Creative and innovative Indonesian learning can foster students' enthusiasm for learning. Students are very interested and very enthusiastic when they see a new and creative learning medium. Objectives: The purpose of this writing is to know the knowledge of standard words Indonesian that students have, and to provide new knowledge about standard Indonesian words for students. Methods: This study uses qualitative methods because the researcher can draw generalizations of what is observed inductively, and abstract theories about processes, actions, or interactions based on the views of the participants studied (Creswell, 2009). The wheel of names is a tool or medium used in learning or coaching Indonesian. Result: The media can be used as a measure of a student’s ability to understand standard and non-standard words. The lack of standard Indonesian words owned by students makes the wheel of names used in learning Indonesian at SMP Negeri 12 Dumai. Conclusion: By using the wheel of names as a learning medium, it is hoped that it can make it easier for students to understand and add new knowledge about the standard word Indonesian.